7-10x=27-24x

Simple and best practice solution for 7-10x=27-24x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-10x=27-24x equation:


Simplifying
7 + -10x = 27 + -24x

Solving
7 + -10x = 27 + -24x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '24x' to each side of the equation.
7 + -10x + 24x = 27 + -24x + 24x

Combine like terms: -10x + 24x = 14x
7 + 14x = 27 + -24x + 24x

Combine like terms: -24x + 24x = 0
7 + 14x = 27 + 0
7 + 14x = 27

Add '-7' to each side of the equation.
7 + -7 + 14x = 27 + -7

Combine like terms: 7 + -7 = 0
0 + 14x = 27 + -7
14x = 27 + -7

Combine like terms: 27 + -7 = 20
14x = 20

Divide each side by '14'.
x = 1.428571429

Simplifying
x = 1.428571429

See similar equations:

| h=16t^2+56t+100 | | 12.5x=-63.75 | | h=16t^2+56+100 | | 4x-7y=28 | | 28y^2-43y+10=0 | | 4x-10=-6x+7 | | 7k+12=5(k+6)-8 | | -25x+y=65 | | -8p=8(p-16) | | -21-4x=3x+16 | | 122-5x=10x+22 | | 154-4x=5x+19 | | 0.08x+0.06(x+9)=1.24 | | 5w+1=7(2-3w) | | 1+5x=41+x | | (10x+9)(7x+1)= | | 5x-(x+3)=2x-9 | | 4(m-6)=-2m | | 6b+9=27 | | (7x+1)= | | 3(4+3u)=2(u-1) | | 5x(x+4)(3x+5)=180 | | 4x+6=2y | | 15y-3=8y+4 | | -0.3x+2.1(x-4)=-6.6 | | 12z^2+13z-4=0 | | 65=X*(2x-3) | | -4+2a=12-15a+a | | (10x+9)= | | y=1x+4 | | -3(m-4)+2(5+2m)=29 | | 11h+21=-8h-36 |

Equations solver categories